1996
DOI: 10.1089/ten.1996.2.241
|View full text |Cite
|
Sign up to set email alerts
|

Surface Roughness, Porosity, and Texture as Modifiers of Cellular Adhesion

Abstract: Substrate topography in the micrometer range is reviewed as a modifier of the response of cultured cells and of biocompatibility when implanted into tissues. Characterization methods for substrate topography are discussed, including scanning electron microscopy, profilometry, laser scanning, and confocal microscopy. Because of the current technical limitations in reproducing micron-level topographic details, only one method, ion-beam etching, has been found suitable for texturing substrates on nonplanar surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(89 citation statements)
references
References 23 publications
2
85
0
2
Order By: Relevance
“…The work was stimulated by almost 40 years of observation that the FBR to an implanted material is modulated by roughness, porosity, and/or texture [20][21][22][23]. Our porous scaffold materials, prepared by sphere templating, are characterized by a single pore size (in contrast to a pore size distribution), with pores spherical in shape and interconnected.…”
Section: The Future Of Biocompatibilitymentioning
confidence: 99%
“…The work was stimulated by almost 40 years of observation that the FBR to an implanted material is modulated by roughness, porosity, and/or texture [20][21][22][23]. Our porous scaffold materials, prepared by sphere templating, are characterized by a single pore size (in contrast to a pore size distribution), with pores spherical in shape and interconnected.…”
Section: The Future Of Biocompatibilitymentioning
confidence: 99%
“…From Figure 3, the groove depth in this study was found to be between 200 and 250 nm. It has been shown that cells such as fibroblasts react to depth as shallow as 70nm [7]. Ridge distance was also found to be an important factor for cell orientation and alignment.…”
Section: Resultsmentioning
confidence: 99%
“…Pores in a tissue-engineered scaffold make up the space in which cells reside. In this study, the majority of pore diameters are limited to the range of 25 to 100 μm (Figures 4-7) According to literature data of vascular grafts, the effective pore diameters for cell ingrowths are between 20 and 60 μm while for bone ingrowths the pore-diameters between 75 and 150 μm are required (35). The pore size that would permit adequate cellular infiltration has been suggested to be greater than 10 μm (9).…”
Section: Morphological Characterization -mentioning
confidence: 86%